Application of Three Diagnostic Serologic Techniques to Detect of Dromedary Camel’s Brucellosis - Mithal Kareem Abass Al-Hassani; Hasanain AJ. Al-Gharban; Luma foad Manher (Al-Qadisiyah Journal of Pure Science, 2018)
This study was aimed to evaluate the prevalence of brucellosis in camel by using of Rose-Bengal test (RBT), Standard-tube agglutination test (STAT) and competitive Enzyme-Linked immunosorbent assay (c-ELISA) for first time in Iraq. From some regions of Al-Qadisiyah governorate, a totally of 148 camels from both sexes were submitted for collection of blood samples, and the overall results showed that 8.78%, 4.1%, and 12.84% of camels were seropositives by RBT, STAT and c-ELISA, respectively. In addition, the cross-classification results have been discussed as follow: by both c-ELISA and RBT, the seropositive result was 7.43%, while, 5.41% by c-ELISA and 1.35% by RBT, only. Whereas, the positive result was 4.1% by both c-ELISA and STAT, while, 8.78% positive camels by c-ELISA, only. In regarding to sex factor, the positive results in female camels were 9.92%, 4.96% and 13.22%; while in males, they were 3.7%, 0% and 11.11% by RBT, STAT and c-ELISA. In association to age factor, ³ 4 years group were reported 13.85%, 7.69% and 18.46%, while in 1-4 years group, they were 4.82%, 1.2% and 8.43% seropositive camels by RBT, STAT and c-ELISA, respectively. Statistically, the significant difference (P£0.05) was reported among the total positive results and within the cross-classification results for applied serological tests. Also, the female camels were showed an infection rate more than males by RBT and STAT, whereas, both sexes were at a similar level of infection by c-ELISA. As well as, > 4 years group were revealed on a high prevalence rate than 1-4 years group by all assays.